Outsourcing outsourcingowi nierówny - wyniki badań - Niemczyk, Jerzy (Outsourcing can be different - research results, 2006)
Outsourcing is slowly getting management classics. The literature review shows it as a homo gencous phenomenon. The aim of this paper is to present its strengths across the processes consli luting a value chain. Additionally this paper shows the necessity of differentiated outsourcing view depending on a topic.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 174-183